The role of rituximab in the therapy of secondary glomerulonephritis. Issue 3 (July 2015) - Quaglia, Marco; Musetti, Claudio; Stratta, Piero
Rituximab (RTX), a B-lymphocytes depleting monoclonal antibody, deeply changed the therapeutic landscape of secondary glomerulonephritis in the past decade. RTX has proved to be as effective as cyclophosphamide in inducing remission in ANCA-associated vasculitis and better than azathioprine as maintenance therapy in three different RCT. Treatment's duration and modality, however, remain debated. RTX has been widely used in resistant or relapsing proliferative lupus nephritis (LN), with positive results reported by retrospective studies; however, when employed as an "add-on" induction therapy in a RCT, it did not show a definite additive effect to standard therapy with mycophenolate mofetil and steroid in moderate forms of LN. In prospect, it remains a promising tool both as second-line therapy for resistant forms and as a "steroid-sparing" agent to strengthen induction and to allow reduced or minimal maintenance therapy. RTX is effective in the treatment of HCV-related cryoglobulinemic vasculitis, including glomerulonephritis. Monotherapy appears more effective than traditional cytostatic drugs in anti-viral drugs resistant forms. Association of RTX with antiviral therapy (pegINFα and ribavirin) produces a more rapid and effective immunological response with a similar virological one. Direct antiviral agents are beginning to be employed in association with traditional ones and RTX with promising results. RTX has been also anecdotally employed in fibrillary glomerulonephritis and in "monoclonal immunoglobulin deposits-related glomerulopathy" (mIgGN) secondary to non-Hodgkin lymphomas, either alone or within the setting of a hematological chemotherapy. Although many aspects need to be clarified, the role of RTX in the treatment of secondary glomerulonephritis has become increasingly important due to a favorable risk/benefit profile.